Hermite-Hadamard type inequalities for new conditions on h-convex functions via ψ-Hilfer integral operators - Benaissa, Bouharket; Azzouz, Noureddine; Budak, Hüseyin (Analysis and mathematical physics, 2024)
We employ a new function class called B -function to create a new version of fractional Hermite–Hadamard and trapezoid type inequalities on the right-hand side that involves h -convex and ψ -Hilfer operators. We also provide new midpoint-type inequalities using h -convex functions.